ORGANIZATIONAL BEHAVIOR ANALYSIS THROUGH THE PERSPECTIVE OF INTERNAL COMMUNICATION IN THE DIGITAL AGE - Witri Cahyati; Sandra Irawaty; Widyapuri Prasastiningtyas; Renata Salsabilla Ramadhan (PT Altin Riset Publishing, 2026)
This study aims to analyze organizational behavior through the perspective of internal communication in the digital age, highlighting how communication practices shape values, assumptions, and the adoption of technological innovations within organizations. The approach used is a systematic literature review, including a search for scientific articles in indexed databases (Scopus, ScienceDirect, Google Scholar) using keywords such as internal communication, digital transformation, organizational behavior, diffusion of innovations, and organizational culture. The selected literature is limited to peer-reviewed publications from 2014 to 2025, thus covering the latest developments in digital communication and organizational culture. The conceptual framework of the study integrates three main theories: Organizational Communication Theory (Heath & Bryant, 2000), the Diffusion of Innovations Model (Rogers, 2003), and Organizational Culture Theory (Edgar H. Schein, 2024). Through thematic analysis, the literature was extracted to identify the relationship between the quality of internal information flow (clarity, consistency, digital channels) and organizational behavior variables such as employee engagement, collaboration, loyalty, and innovation adoption rates. The synthetic results show that digitally integrated internal communication accelerates the process of innovation diffusion, strengthens shared cultural values, and increases participation and job satisfaction levels. Conversely, fragmented communication has the potential to cause resistance, conflict, and decreased productivity. This study contributes theoretically by expanding the understanding of the communicative role in organizational digital transformation, as well as practical implications for HR managers and change leaders to design communication strategies that balance information disclosure, message consistency, and cultural support to facilitate adaptive and innovative organizational behavior.